EVALUASI KERENTANAN KEAMANAN JARINGAN NIRKABEL MENGGUNAKAN METODE PENETRATION TESTING DENGAN AIRCRACK-NG - Fathul Anam; Fahmi Fachri (Rabit : Jurnal Teknologi dan Sistem Informasi Univrab, 2025)
Technological advancements in networking have become an essential component in the information processes of society. With the increasing use of wireless networks, understanding the security of networks connected to the internet is crucial to protect them from hacker attacks. Penetration testing is the first step to improving network security. This study aims to identify and exploit vulnerabilities in wireless networks within the pesantren environment using the Aircrack-ng tool with a dictionary attack technique. The analysis results revealed vulnerabilities, such as weak passwords and a lack of encryption, which could be exploited by malicious actors. Based on these findings, it is recommended to use more complex passwords and update security protocols to strengthen the network defense system. The impact of this study is expected to raise awareness and understanding of the importance of penetration testing in identifying and addressing potential vulnerabilities. Additionally, the results of this research are expected to make a significant contribution to protecting wireless networks in educational institutions, particularly pesantren, from the growing threats of cyberattacks